Find the complete integral of p+q=x+y
Solution
Let’s consider the transformation α = x – y, β = y
Inverse transformation is x = α + β, y = β
Let u(x, y) = v(α, β). Then, we have
p + q = ux + uy = vα (∂α/∂x) + vβ (∂β /∂x) + vα (∂α/∂y) + vβ (∂β /∂y) = vα - vα + vβ = vβ
Therefore, the partial differential equation becomes
vβ = α + 2β
Integrating this equation
v = α β + β2 + g(α)
Here g(α) is an arbitrary function of α.
So u(x, y) = α β + β2 + g(α) = (x – y)y+y2 + g(x – y) = x y + g(x – y)
Answer
u(x, y) = x y + g(x – y), where g(α) is an arbitrary function of α.
Comments
Leave a comment